Hubungan Antara Kejadian dan Jenis Anemia dengan Kejadian Hiperemesis Gravidarum pada Ibu Hamil: Studi Observasional di Rumah Sakit Jiwa Daerah Dr. Amino Gondohutomo Periode 2022-2025 - Fabella Ade Kusumawati, Njoo; Yulice Soraya Nur Intan (Journal of Medical Practice and Research, 2026)
Hyperemesis gravidarum is an incident of persistent nausea and vomiting that begins early in pregnancy and continues until 20 weeks of gestation. The causes of hyperemesis gravidarum are influenced by many factors, including maternal nutrition and physiological changes, which can be characterized by anemia and the type of anemia. This study aims to determine the relationship between the incidence of anemia and the type of anemia with the incidence of hyperemesis gravidarum in pregnant women at Dr. Amino Gondohutomo Mental Hospital, Semarang. This observational study used a case-control method using secondary data from the medical records of pregnant women at Dr. Amino Gondohutomo Mental Hospital. Sampling was performed using consecutive sampling, meeting inclusion and exclusion criteria during period from 2022 to 2025. Data were analyzed using the chi-square test for anemia incidence and Fisher's exact test for anemia type. The sample size was 68 pregnant women: 34 with hyperemesis gravidarum and 34 without hyperemesis gravidarum. The test results showed a significant relationship with a p-value of 0.028 (p < 0.05) between the incidence of anemia and HEG. The most common type of anemia is normocytic normochromic, and the test results showed a significant relationship between the type of anemia and HEG at p = 0.001 (p < 0.05).